2011
DOI: 10.3892/or.2011.1229
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic apoptosis in human acute myeloid leukemia (AML): primary human AML cells expose calreticulin and release heat shock protein (HSP) 70 and HSP90 during apoptosis

Abstract: Abstract. several previous studies have demonstrated that both conventional cytotoxic drugs as well as targeted therapeutics can induce apoptosis in primary human acute myelogenous leukemia (AMl) cells. However, the apoptotic phenotype of dying AMl cells has been less extensively characterized. even though specific antileukemic immune reactivity is important in AMl, especially for allotransplanted patients, it has not been investigated whether dying primary human AMl cells show phenotypic characteristics consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Apoptotic AML cells collected during in vivo therapy with all- trans retinoic acid showed increased exposure of CRT during spontaneous in vitro apoptosis, suggesting that in vivo pharmacotherapy can induce ICD. 29 But the authors detected a wide variation of the level of CRT exposure between patients, which probably depends on individual patient characteristics. 29 It has also been shown that serum CRT levels are significantly higher in lung cancer patients after chemotherapy compared to untreated patients.…”
Section: Role Of Crt Surface Exposure During Icd In Cancer Treatmentmentioning
confidence: 98%
“…Apoptotic AML cells collected during in vivo therapy with all- trans retinoic acid showed increased exposure of CRT during spontaneous in vitro apoptosis, suggesting that in vivo pharmacotherapy can induce ICD. 29 But the authors detected a wide variation of the level of CRT exposure between patients, which probably depends on individual patient characteristics. 29 It has also been shown that serum CRT levels are significantly higher in lung cancer patients after chemotherapy compared to untreated patients.…”
Section: Role Of Crt Surface Exposure During Icd In Cancer Treatmentmentioning
confidence: 98%
“…The use of such an approach as a low-toxicity strategy in older patients is supported by several observations. First, primary human AML cells can undergo immunogenic apoptosis with exposure of calreticulin, and release heat shock protein 70 (HSP70) and heat shock protein 90 (HSP90); this may initiate or enhance the development of antileukemic T cell reactivity [115]. Second, a prognostic impact of serum heat shock protein (HSP) levels has been suggested [116-119], possibly caused by soluble HSPs that facilitate immunogenic presentation of the client proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In AML cells, cytarabine, daunorubicin, all-trans retinoic acid (ATRA) and valproic acid were also found to induce increased calreticulin exposure (ecto-CRT) and release of HSP70 and HSP90, which indicating an induction of immunogenic apoptosis, although the level of CRT exposure/HSP release seems to depend on individual patients characteristics rather than the apoptosis-inducing drug [102]. Bortezomib had been showed to induce immunogenic death of human multiple myeloma, including primary tumor cells, which is dependent on cell-cell contact and linked to the expression of Hsp90 on the surface of dying cells [103]. More recently, diverse pro-apoptotic drugs, including topoisomerase II inhibitors, kinase inhibitors, and proteosome inhibitors have been shown to activate pannexin-1 channels and ATP release in Jurkat T cell acute lymphocytic leukemia model, which mediate immunogenic anti-tumor responses [104].…”
Section: The Role Of Autophagy Autophagy-associated Adaptive Immunitmentioning
confidence: 99%